Pengaruh Variasi Konsentrasi Zno Pada Karbon Aktif Terhadap Band Gap Setelah Impregnasi - Dwi Cintya Rori; Mutiara Syabila (Publikasi Indonesia, 2022)
ZnO semiconductors are good photocatalysts for degrading volatile organic pollutants into CO2 and H2O. Activated carbon has a high absorption capacity, and contains amorphous carbon. The purpose of this study was to determine the effect of variations in the concentration of ZnO on activated carbon on the band gap after impregnation. Determination of Bandgap value was determined using UV-DRS with the Tauc Plot method. The effect of variations in ZnO concentration on activated carbon on the band gap after impregnation shows the band gap value. The change in band gap value is caused by electron resonance when electrons from ZnO interact with polycyclic aromatic activated carbon. At the 20% variation there is a widening of the band gap value caused by a short wavelength shift. The conclusion obtained is that the characteristics of the AC-ZnO catalyst have band gap values ​​for each variation, namely 2.69 eV, 2.7 eV, 2.97 eV, 4.85 eV and 3.0 eV. The band gap values ​​increased with increasing concentrations of ZnO 5%, 10% and 15%.